Clinical outcomes of neuroendoscopic resection of brain abscess guided by electromagnetic navigation among patients presenting at Jieyang People's Hospital in China - Mindong Huang; Jiandan Zou (Heliyon)
Background: The treatment of brain abscesses presents certain difficulties. How to enhance the surgical effect and the positive rate of bacterial culture has always been our objective. Aim: This study explored the surgical outcome of neuroendoscopic resection of brain abscess under the guidance of electromagnetic navigation and how to increase the positive rate of bacterial culture. Methods: From June 2018 to December 2023, a total of 5 cases of neuroendoscopic resection of brain abscess under the guidance of electromagnetic navigation were conducted in our hospital. After admission, enhanced head MR layer scans were carried out. The imaging data were imported into the neuronavigation system. After successful registration, the abscess wall was cauterized with bipolar under the guidance of electromagnetic navigation, and the abscess wall was taken for bacterial culture and drug sensitivity test. We calculated the positive rate of bacterial culture, that is, the positive rate of bacterial culture is the number of positive cases of bacterial culture divided by the total number of cases sent for culture. After the operation, sensitive antibiotics were intravenously administered according to the bacterial culture and drug sensitivity test. Results: The headache symptoms of the 5 patients were significantly alleviated, and there was no residual limb dysfunction. Reexamination of the head MR indicated that the abscess was significantly reduced. Five cases were all subjected to bacterial culture, among which bacteria were cultured in three cases, and the positive rate of bacterial culture was 60 %. The abscess clearance rate after the operation was all greater than 80 %. Conclusion: Neuroendoscopic resection of brain abscess under the guidance of electromagnetic navigation has a favorable effect.This surgical method increases the positive rate of bacterial culture and holds significant reference significance for the subsequent intravenous administration of antibacterial drugs.